Valorização e uso agrícola de resíduos orgânicos da cadeia produtiva de frango de corte como alternativa para a economia circular - Chiarelotto, Maico (2022)
The objective of the study was to evaluate the effects of different organic composts from broiler production chain wastes and their combination with mineral fertilizers on soil quality, nutritional status, and corn productivity. The experiment was conducted in the Experimental Nucleus of Agricultural Engineering of the State University of Western Paraná, Cascavel, Paraná, Brazil. The experiment was installed in September 2016 and finalized in December 2020. The agricultural crop chosen to evaluate the performance of the fertilization proposal was corn. During the experimental period, four crops were harvested. The experimental design was defined in randomized blocks, with six treatments and three repetitions, totaling 18 plots. The treatments were characterized by the combination of mineral fertilizer and organic compost. The reduction in the amount of mineral fertilizer and organic compost applied over the four corn crops was also observed. The organic composts applied were characterized by physicochemical parameters and compared with limits defined by local legislation. The effects on the soil were evaluated by soil density, total porosity, microporosity, macroporosity, pH, available P, K, Zn, Cu, Mn, Fe, total organic carbon, carbon sequestration, and chemical fractioning of organic matter with the application of Fourier transform infrared spectroscopy. The response of corn to the fertilization strategy was evaluated by foliar diagnosis of nutritional status and yield. The organic composts C30, C60 and CAF presented physicochemical parameters according to the Normative Instructions No. 35/2006, 7/2016, 61/2020, and CONAMA Resolution 481/2017. The TOC concentration for CCM was below the minimum required limit (15%) for all four years of analysis. After four years of experiment, the soil organic carbon content was significantly affected by the addition of organic compounds, especially in the 0-0.1 m soil layer. Treatments C60 and CTA showed higher concentrations (4.10 and 4.07%), stocks (50.13 and 49.69 Mg/ha), sequestration rate (2.99 Mg/ha.year) and carbon sequestration efficiency (70.09 and 74.47%), in the 0-0.1 m layer. The largest reductions in density and increase in total porosity were verified for treatments C30, C60, and CTA, compared to the control. The greatest changes occurred in the 0-0.1 m soil layer. The addition of organic compost raised the pH and reduced soil acidity for all treatments compared to the control, especially for C60 (pH: 6.10) and CTA (pH: 6.17). The addition of organic compounds to the soil increased the concentration of microelements such as Zn, Fe, Mn and Cu. The gradual reduction of mineral fertilizers by 30, 40, 50, and 60% with the addition of organic composts maintained the nutritional quality of corn plants compared to 100% mineral fertilization. Even with the reduction of mineral fertilizers, the organic composts were able to supply the nutritional demand of the plants, without causing reduction in productivity. Physical properties and soil nutrients, leaf diagnosis, and corn productivity demonstrated the capacity of the combination between organic composts and mineral fertilizers. The strategy adopted in this study can promote the valorization of broiler production chain wastes and, consequently, the circular economy in this sector.